2018
DOI: 10.1111/trf.14461
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses and ordering practices driving blood demand for treatment of anemia in Tanzania

Abstract: Strategies to prevent and treat underlying causes of anemia and decrease inappropriate blood requests will likely increase blood availability. Restrictive blood ordering practices seen in adults with severe anemia suggests undertreatment of anemia and may result in an underestimation of the national blood demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…However, adherence to the guidelines is variable [ 11 ]. Blood transfusions are often given without laboratory confirmation of Hb level [ 12 ] or documented indications [ 13 ], and patients with indications for transfusions are not given blood [ 14 ]. Most of the studies that examined clinical use of blood amongst children have done so in children with a known pre-transfusion Hb level [ 4 , 6 , 15 ] usually under controlled research settings [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, adherence to the guidelines is variable [ 11 ]. Blood transfusions are often given without laboratory confirmation of Hb level [ 12 ] or documented indications [ 13 ], and patients with indications for transfusions are not given blood [ 14 ]. Most of the studies that examined clinical use of blood amongst children have done so in children with a known pre-transfusion Hb level [ 4 , 6 , 15 ] usually under controlled research settings [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major etiologies related to OH included all types of abortion (68%) and ectopic pregnancy (27%); the number of recorded etiologies exceeded the number of women designated as having OH. Hemorrhage etiologies were associated with gestational (26) 15 (12) 24 (13) 28 (20) 39 (87) 75 (29) 17 (15) No 43 (12) 18 (15) 20 (16) 5 (4) 17 (9) 22 (16) 4 (9) 34 ( (12) 19 (15) 21 (16) 44 (24) 6 (4) 1 (2) 31 (12) 23 (22) Anemia 29 (8) 16 (14) 7 (6) 6 (5) 5 (3) 7 (5) 17 (38) 28 (11) 1 (1) Other 43 (12) 11 (9) 19 (15) 13 (10) 19 (11) 22 (16) 2 (4) 31 (12) 12 (12) Missing 91 (25) 28 (24) 36 (29) 27 (21) 37 (21) 32 (23) 18 (40) 65 (24) 26 (25) * Eight trimester values missing. † Chi-square p values contrast the three levels shown.…”
Section: Resultsmentioning
confidence: 99%
“…While not as well formalized in low‐middle‐income countries, patient blood management strategies (including single‐unit transfusions with reassessment and/or hemoglobin measurement in the stable nonbleeding patient rather than routine double‐unit transfusions) are very relevant given pervasive challenges surrounding blood availability. Ironically, despite shortfall in provision of blood, inappropriate transfusion and overtransfusion is not uncommon, and likely stems from relatively little education in transfusion medicine, coupled with a lack of standardization of transfusion practices as reflected by nonadherence to evidence‐based guidelines . Pertinent to the obstetric population, the Network for the Advancement of Patient Blood Management, Haemostasis and Thrombosis in collaboration with the International Federation of Gynaecology and Obstetrics and the European Board and College of Obstetrics and Gynaecology have published recommendations on prenatal iron therapy that could mitigate risk of transfusion .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in Tanzania found that 17% of requested units were deemed inappropriate. 95 A survey of seven African countries found that none of the participating countries had any personnel who were exclusively trained in transfusion medicine, and only one had standing operational protocols. 19 The level of training among prescribers also varies greatly.…”
Section: Rational Blood Usementioning
confidence: 99%